From Student-Centered Learning to Student Agency: A Systematic Review of Motivation, Self-Regulated Learning, and Academic Achievement in the Merdeka Curriculum with ASEAN Perspectives - Putri Dwi Erwanti; Suratno (Jurnal Paedagogy, 2026)
This study aims to synthesize the influence of learning motivation and self-regulated learning on students’ academic achievement in the implementation of the Merdeka Curriculum among senior high school students, while benchmarking pedagogical strategies against those implemented in ASEAN countries. The study employed a Systematic Literature Review (SLR) design following the PRISMA 2020 protocol. A total of 20 empirical studies published between 2020 and 2025 were retrieved from the Scopus, Google Scholar, and SINTA databases. Data were analyzed using a thematic synthesis technique. The findings indicate that learning motivation and self-regulated learning make a substantial contribution to students’ academic achievement in the Indonesian context, with the highest reported effect size reaching 88.9%. Comparative analysis reveals that several ASEAN countries have more extensively advanced student autonomy through the integration of self-monitoring technologies (e.g., Singapore and Vietnam) and strong teacher autonomy support (e.g., Malaysia and Thailand). These findings suggest that optimizing the implementation of the Merdeka Curriculum requires the adoption of such pedagogical strategies. In particular, the roles of teachers and educational technology should be transformed from administrative support mechanisms into key drivers that foster student agency. Overall, this study highlights the importance of aligning motivation, self-regulated learning, and innovative pedagogical practices to enhance academic achievement in contemporary educational contexts.